Performance of next-generation sequencing for diagnosis of blood infections by Klebsiella pneumoniae - Wang, Lei; Liu, Na; Zhang, Lin; Cui, Likun; Zhu, Mengdie; Li, Zhifang; Wang, Panpan; Wang, Zhengbin (Frontiers in Cellular and Infection Microbiology, 2023)
Objective ： Klebsiella pneumoniae (Kp) bloodstream infections (BSI) can be a life-threatening opportunistic infection. We aimed to evaluate the diagnostic accuracy of metagenomic next-generation sequencing (mNGS) for Kp BSI.We retrospectively analyzed 72 patients suspected with bloodstream infection and mNGS Kp positive in peripheral blood, who were hospitalized in our hospital from January 2022 to January 2023. Clinical data and laboratory parameters were collected. All patients had blood drawn and other samples for blood mNGS, blood cultures(BC) and other cultures(OC). The accuracy of mNGS results was analyzed according to infection site, clinical indicators, therapeutic effect and routine culture results. The detection of pathogenic microorganisms by blood mNGS and routine culture was compared.Results: Among 72 infection patients, 29 cases (40.28%) were BC positive, 43 cases (59.72%) were other culture (OC) positive, 16 cases (22.22%) were both BC and OC positive, 56 cases were positive for both mNGS and routine culture. Among the 56 double-positive cases, mNGS and conventional cultures were completely consistent in 27 cases, partially consistent in 15 cases, and completely inconsistent in 14 cases. Using the clinical diagnosis as the reference standard, There were 51 cases consistent with the results of mNGS with Kp BSI, the clinical consistency was 70.83% (51/72). The coincidence rate of mNGS and clinical diagnosis was higher than that of BC (54.17%, 39/72), indicating a statistically significant difference between the two methods (P<0.01).Current evidence indicates that mNGS exhibits excellent accuracy for the diagnosis of Kp BSI. Although it cannot replace blood culture detection technology, it can be used as a supplement to provide stronger diagnostic capabilities for BSI and optimize treatment.